The characteristic of functional fermented caprine milk - Biadała, Agata; Pikul, Jan; Rudzińska, Magdalena; Majcher, Małgorzata; Lasik-Kurdyś, Małgorzata; Szablewski, Tomasz; Cegielska-Radziejewska, Renata (Emirates Journal of Food and Agriculture, 2019)
The aim of this study was to characterize functional fermented caprine milk. Functional properties of fermented milks was an effect of increasing the level of whey proteins, MUFA and PUFA content in final product Milk used for experiments was obtained from experimental station belonging to Poznań University of Life Sciences. Feeding strategy was included modification by adding 12% of Camelina sativa cake. The fermentation process was done by using Lactobacillus acidophilus, Lactobacillus spp., and kefir grain microflora. The quality properties which were considered was metabolic activity, monosaccharide, disaccharide, lactic acid and ethanol content, aroma and fat profile. It was noted that increasing the content of functional components in processed milk caused changes in lactose, MUFA, PUFA and volatile acids content in final product.